STRATEGI HUMAS DALAM MENINGKATKAN CITRA SEKOLAH DI SMP AN-NUR II BULULAWANG DAN SMP AL- IZZAH KOTA BATU - Ummah, Kuntum Khaira; Imam Muslimin; Abdul Aziz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Public Relations is the spearhead of a school and is a reflection of an institution to the public. Therefore, public relations must be able to establish good relationships with stakeholders in order to establish good relationships and positive views of the school to get a positive image from the institution. The type of research used is qualitative. The data collection methods are interviews, observations, and documentation. The results of this study are: 1. Public relations strategy planning in improving the image of the school at SMP An-Nur II Bululawang and SMP Al-Izzah Kota Batu has differences both from history, school programs, vision and mission, strengths, opportunities, weaknesses and threats faced are also different. This program will be discussed during the meeting. 2. Implementation of public relations strategies in improving the image of schools at SMP An-Nur II Bululawang and SMP Al-Izzah Kota Batu, implementing work programs that have been set and realizing school programs that are tailored to their respective fields. 3. The results of the public relations strategy in improving the image of the school at SMP An-Nur II Bululawang and SMP Al-Izzah Kota Batu have a positive effect on the image of the two schools, both because of the history, facilities, services, and achievements of the school achieved by the institution.